Literature Review: Pemanfaatan Building Information Modeling (BIM) dalam Konstruksi sebagai Alat Komunikasi dan Kolaborasi dalam Integrated Project Delivery (IPD) - Firman Parama Yudha; Ahmad Saifudin Mutaqi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Building Information Modeling (BIM) is a technology increasingly used in the modern construction industry, particularly to improve communication efficiency and collaboration between stakeholders. This technology enables the integration of project data and information into a comprehensive digital model, allowing all involved parties to access, verify, and update information in real time. This study aims to evaluate the strategic role of BIM as a communication medium in the Integrated Project Delivery (IPD) approach, focusing on the planning stage involving the disciplines of architecture, structure, and Mechanical, Electrical, and Plumbing (MEP) systems. The IPD approach emphasizes cross-disciplinary collaboration from the early stages of a project to optimize outcomes, reduce risks, and accelerate completion. The research methods used are literature review and case study analysis of various projects that have implemented BIM within the IPD framework. The data analyzed include the effectiveness of information exchange, inter-team coordination, and early identification of design conflicts. The study results show that BIM significantly improves information transparency among stakeholders, minimizes the risk of miscommunication, and accelerates the decision-making process through accurate and integrated data visualization. BIM models also facilitate the detection of potential conflicts, such as clashes between structural and MEP elements, before entering the physical construction phase, thereby reducing repair costs and delays. Furthermore, the use of BIM in IPD fosters a more collaborative work culture, where architects, engineers, and contractors can work together to solve problems quickly and effectively. Thus, BIM has proven to play a crucial role as a primary communication tool in IPD implementation, while also serving as a crucial foundation for achieving efficient, integrated, and high-quality construction project management.